Non-melanoma skin cancer: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Newlands, C; Currie, R; Memon, A; Whitaker, S; Woolford, T
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. This paper provides consensus recommendations on the management of cutaneous basal cell carcinoma and squamous cell carcinoma in the head and neck region on the basis of current evidence. Recommendations: Royal College of Pathologists minimum datasets for NMSC should be adhered to in order to improve patient care and help work-force planning in pathology departments. (G) Tumour depth is of critical importance in identifying high-risk cutaneous squamous cell carcinoma (cSCC), and should be reported in all cases. (R) Appropriate imaging to determine the extent of primary NMSC is indicated when peri-neural involvement or bony invasion is suspected. (R) In the clinically N0 neck, radiological imaging is not beneficial, and a policy of watchful waiting and patient education can be adopted. (R) Patients with high-risk NMSC should be treated by members of a skin cancer multidisciplinary team (MDT) in secondary care. (G) Non-infiltrative basal cell carcinoma (BCC) <2 cm in size should be excised with a margin of 4–5 mm. Smaller margins (2–3 mm) may be taken in sites where reconstructive options are limited, when reconstruction should be delayed. (R) Where there is a high risk of recurrence, delayed reconstruction or Mohs micrographic surgery should be used. (R) Surgical excision of low-risk cSCC with a margin of 4 mm or greater is the treatment of choice. (R) High-risk cSCC should be excised with a margin of 6 mm or greater. (R). Mohs micrographic surgery has a role in some high-risk cSCC cases following MDT discussion. (R) Delayed reconstruction should be used in high-risk cSCC. (G) Intra-operative conventional frozen section in cSCC is not recommended. (G) Radiotherapy (RT) is an effective therapy for primary BCC and cSCC. (R) Re-excision should be carried out for incompletely excised high-risk BCC or where there is deep margin involvement. (R) Incompletely excised high-risk cSCC should be re-excised. (R) Further surgery should involve confirmed marginal clearance before reconstruction. (R) P+ N0 disease: Resection should include involved parotid tissue, combined with levels I–III neck dissection, to include the external jugular node. (R) P+ N+ disease: Resection should include level V if that level is clinically or radiologically involved. (R) Adjuvant RT should include level V if not dissected. (R) P0 N+ disease: Anterior neck disease should be managed with levels I–IV neck dissection to include the external jugular node. (R) P0 N+ posterior echelon nodal disease (i.e. occipital or post-auricular) should undergo dissection of levels II–V, with sparing of level I. (R) Consider treatment of the ipsilateral parotid if the primary site is the anterior scalp, temple or forehead. (R) All patients should receive education in self-examination and skin cancer prevention measures. (G) Patients who have had a single completely excised BCC or low-risk cSCC can be discharged after a single post-operative visit. (G) Patients with an excised high-risk cSCC should be reviewed three to six monthly for two years, with further annual review depending upon clinical risk. (G) Those with recurrent or multiple BCCs should be offered annual review. (G)